Isolation and selection of lactic acid bacteria with probiotic potential from raw goat milk - Contreras de la Hoz, Rubén
This research shows the detailed process chosen to isolate and select lactic acid bacteria with probiotic potential, from a typical ecological niche such as goat milk. In which 5 strains were isolated, these being the ones that appeared the closest characteristics to this group of bacteria, after this, different safety tests were carried out, with the aim of evaluating their probiotic potential, which are: Acidifying activity, CO2 production, Milk aroma production, Pathogen inhibition capacity, Resistance to gastric acidity and haemolytic activity. Obtaining as a result of these 5 strains only 2 with probiotic potential. With our research we observed that goat milk can be used in the manufacture of a wide variety of dairy products, it can also be used as a vehicle for functional components such as “prebiotic substances or probiotic bacteria”. However, in these probiotics/ prebiotics, it is still minimally explored, regarding the functional aspects of dairy products derived from goat’s milk.